ANALISIS FAKTOR–FAKTOR YANG MEMPENGARUHI FOREIGN DIRECT INVESTMENT DI NEGARA BERKEMBANG KAWASAN ASIA - Ananda, Caesario Fajry; Saputra, Putu Mahardika Adi (Journal of Development Economic and Social Studies, 2024)
Foreign Direct Investment (FDI) holds a crucial role, benefing not only the investor's home country but also contributing to the prospery of the host nations, especially the developing countries in the Asian region, which stand as the largest recipients of global FDI. This research aims to pinpoint the factors influencing FDI inflows in Asian developing countries from 2012 to 2019. Employing panel data analysis techniques, the study reveals that market size, trade openness, and infrastructure significantly drive FDI inflows. Conversely, human capal and taxation are identified as hindering factors, while the perception of corruption does not notably impact FDI. By enhancing our comprehension of the dynamics shaping FDI trends in Asian developing nations, this research provides valuable insights for policymakers and stakeholders. serves as a guide for those seeking to create an environment conducive to foreign investment, facilating sustainable economic growth and development in the region.